Collapse mechanism of the thin-walled functionally graded cylinders encased in the saturated permeable mediums. (1st November 2019) - Li, Zhaochao; Zheng, Junxing; Chen, Yizheng; Zhang, Zhen
Highlights: The material property of the FGM cylinder is non-symmetrical to the mid-surface. The buckling behavior of confined FGM cylinder is different from unconfined one. The confined FGM cylinder sustains a higher buckling pressure than the unconfined one. The mechanical behavior of FGM cylinder is different from the homogeneous cylinder. The analytical buckling pressure is obtained and verified by the numerical result. Abstract: This paper investigates the stability behavior of the thin-walled functionally graded material (FGM) cylinders encased in the saturated permeable mediums. Water pressure generates at the outer surface of the cylinder, resulting in "single-lobe" or "two-lobe" deformations due to the confinement of the medium. The critical buckling pressure of the FGM cylinder is obtained analytically by exploring the total potential energy function. It is found that the two-lobe deformation sustains a higher pressure capacity than the single-lobe deformation. A two-dimensional (2D) finite element model (FEM) is developed to obtain the maximum pressure (buckling pressure) by plotting the pressure-displacement equilibrium curves. The comparison shows that the analytical solutions are in very close agreement with the numerical results in terms of the buckling pressure, as well as the equilibrium paths. Finally, the effect of volume fraction exponent ( n ) on the hoop strain, stress, force and bending moment through the cylinder wall is fully examined, indicating the non-symmetrical distribution of the material properties to the mid-surface of the FGM cylinder has a significant influence on the buckling pressure.